Engineering Photoactivatability in Genetically Encoded Voltage and pH Indicators - Lee, Sungmoo; Song, Yoon-Kyu; Baker, Bradley J. (FRONTIERS MEDIA SA, 2019)
Genetically-encoded indicators of neuronal activity enable the labeling of a genetically defined population of neurons to optically monitor their activities. However, researchers often find difficulties in identifying relevant signals from excessive background fluorescence. A photoactivatable version of a genetically encoded calcium indicator, sPA-GCaMP6f is a good example of circumventing such an obstacle by limiting the fluorescence to a region of interest defined by the user. Here, we apply this strategy to genetically encoded voltage (GEVI) and pH (GEPI) indicators. Three photoactivatable GEVI candidates were considered. The first one used a circularly-permuted fluorescent protein, the second design involved a Forster resonance energy transfer (FRET) pair, and the third approach employed a pH-sensitive variant of GFP, ecliptic pHluorin. The candidate with a variant of ecliptic pHluorin exhibited photoactivation and a voltage-dependent fluorescence change. This effort also yielded a pH-sensitive photoactivatable GFP that varies its brightness in response to intracellular pH changes.
Keywords: FLUORESCENT-PROTEIN; ACTION-POTENTIALS; GREEN; DYNAMICS; SENSORS; GFP